Pendidikan Berbasis Budaya Lokal Tarian Hegong Maumeredalam Membentuk Karakter Siswa di SDI C-III Wolomarang Kabupaten Sikka - Benyamin Regi (Educational Journal, 2026)
This study aims to analyze the implementation of local culture-based education through the Hegong Maumere traditional dance in shaping students’ character at SDI C-III Wolomarang, Sikka Regency. Character education at the elementary school level serves as a fundamental foundation for developing students’ personalities rooted in national cultural values. Amid globalization challenges that potentially erode local identity, integrating local culture into the learning process becomes a relevant strategy to instill moral and social values. Hegong dance, as a cultural heritage of the Maumere community in Sikka Regency, embodies values such as togetherness, discipline, responsibility, cooperation, and cultural pride. This research employed a qualitative descriptive approach. Data were collected through participatory observation, in-depth interviews, and documentation. Data analysis followed Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that the integration of Hegong dance into extracurricular activities and arts education significantly contributes to shaping students’ discipline, self-confidence, responsibility, cooperation, and appreciation of local culture. Therefore, local culture-based education proves effective as a strategy for strengthening character education in elementary schools.